2022
DOI: 10.1021/acs.est.2c01782
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic Ligands on the Redox Properties of Fe(II) as Determined by Mediated Electrochemical Oxidation

Abstract: Fe­(II) has been extensively studied due to its importance as a reductant in biogeochemical processes and contaminant attenuation. Previous studies have shown that ligands can alter aqueous Fe­(II) redox reactivity but their data interpretation is constrained by the use of probe compounds. Here, we employed mediated electrochemical oxidation (MEO) as an approach to directly quantify the extent of Fe­(II) oxidation in the absence and presence of three model organic ligands (citrate, nitrilotriacetic acid, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…11,64,65 For example, the standard reduction potential (E H 0 ) of Fe(III)-acetate/Fe(II)-acetate is 0.63 V, 21 while the E H 0 of uncomplexed Fe(III)/Fe(II) is 0.77 V. 66 A recent study showed that at redox potentials at which uncomplexed Fe(II) was observed to be stable (e.g., 0.1 V at pH 7), certain Fe(II) complexes [Fe(II)-citrate and Fe(II)-NTA] were observed to be partially oxidized. 21 Direct evidence of Fe(II) oxidation by DOM was given by Daugherty et al, who observed 40% oxidation of Fe(II) by untreated leonardite humic acid (LHA) under anoxic conditions. 24 Further support for the anoxic oxidation of complexed Fe(II) is given by Bhattacharyya et al, who reacted Fe(II) with the amino acids cysteine, arginine, and histidine and observed that 20−38% of Fe(II) bound to these amino groups was oxidized under anoxic conditions in less than 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,64,65 For example, the standard reduction potential (E H 0 ) of Fe(III)-acetate/Fe(II)-acetate is 0.63 V, 21 while the E H 0 of uncomplexed Fe(III)/Fe(II) is 0.77 V. 66 A recent study showed that at redox potentials at which uncomplexed Fe(II) was observed to be stable (e.g., 0.1 V at pH 7), certain Fe(II) complexes [Fe(II)-citrate and Fe(II)-NTA] were observed to be partially oxidized. 21 Direct evidence of Fe(II) oxidation by DOM was given by Daugherty et al, who observed 40% oxidation of Fe(II) by untreated leonardite humic acid (LHA) under anoxic conditions. 24 Further support for the anoxic oxidation of complexed Fe(II) is given by Bhattacharyya et al, who reacted Fe(II) with the amino acids cysteine, arginine, and histidine and observed that 20−38% of Fe(II) bound to these amino groups was oxidized under anoxic conditions in less than 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…We first examine the possible electron transfer from Fe­(II). Complexation of Fe­(II) by POM may alter its reduction potential ( E H ), similar to the change in E H upon complexation with organic ligands. ,, For example, the standard reduction potential ( E H 0 ) of Fe­(III)-acetate/Fe­(II)-acetate is 0.63 V, while the E H 0 of uncomplexed Fe­(III)/Fe­(II) is 0.77 V . A recent study showed that at redox potentials at which uncomplexed Fe­(II) was observed to be stable (e.g., 0.1 V at pH 7), certain Fe­(II) complexes [Fe­(II)-citrate and Fe­(II)-NTA] were observed to be partially oxidized .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron (Fe) oxides serve as an rusty sink that can protect organic carbon (OC) from decomposition through the formation of Fe–OC complexes. However, Fe oxides can serve as terminal electron acceptors in microbially mediated dissimilatory Fe­(III) reduction in anaerobic or alternating redox environments, leading to the release of Fe-bound OC. Additionally, Fe­(II) can react with H 2 O 2 to generate the reactive oxygen species that can enhance the oxidation of OC. , The rhizosphere of plants under short-term or long-term flooding is a typical environment in which these dual roles of Fe oxides may coexist. Plants growing under flooding conditions can deliver O 2 from the shoot to the root and soil/sediment, thereby promoting the formation of Fe oxides and Fe–OC complexes in the rhizosphere. , The Fe oxides commonly precipitate on the root surface, which are termed Fe plaques. , In addition, the input of labile root exudates and other less decomposable rhizodeposits creates microbial hot spots in the rhizosphere. As a result of accumulation of Fe oxide in the rhizosphere, the abundance of the microbial community and the dissimilatory Fe­(III) reduction rates in the rhizosphere are relatively greater than in the bulk soil/sediment. Overall, the carbon pool of the rhizosphere is strongly affected by Fe oxidation–carbon sequestration and Fe reduction–carbon mineralization, and the influencing factors include radial oxygen loss (ROL), root exudates, the microbial community, manganese, etc. , …”
Section: Introductionmentioning
confidence: 99%